Performance measurement of Tehran railway exploitation company base on the concept of balance score card - mehdi haghighi kashef; foad sadeghi (مطالعات مدیریت بهبود و تحول, 2008)
After 30 years of professional work, Tehran railway exploitation company transfers more than 1.5 million passenger in Tehran and it's suburbs, but still challenges with Performance measurement like other governmental companies. It is difficult for management of such companies, that are naturally non-profit organizations, to improve the performance using Ineffective methods of traditional performance systems that are primarily based on financial criterions. Using balance score card model that simultaneously with financial aspects performs the appraisal relying on three aspects of customer, process, learning and growing, can create efficient appraisal system for managers of these companies. The base of this research, is performance appraisal of TRE company with BSC model, and the main question is that whether performance of TRE company is balanced or not? So, performance of this company was studied in four aspects, using 23 measures including 14 quantity measure created by performance of company and 9 quality measures produced by distributing 1800 questionnaires. Then each index related to any measures is calculated and after combination of scores created by performance appraisal TRE Company and outcome of research shows that study by BSC model is balanced.